DAMPAK KUALITAS LAYANAN DAN HARGA PADA KEPUASAN KONSUMEN (STUDI KASUS PADA KONSUMEN KITAKITA FS) - Liliana Dewi; Tania Callista (STIE Mahardhika, 2020)
KITAKITA FS is a company engaged in food and beverage. The movement of the food and beverage industry with a very rapid increase is one of the things that drives KITAKITA FS in establishing a company. Service quality and price are factors that support customer satisfaction and customer satisfaction is the main factor that supports business continuity. Therefore, this study aims to determine the effect of service quality and price on customer satisfaction KITAKITA FS. This research is quantitative research. The method used in this study is multiple linear analysis. The population in this study was 257 consumers who had come to KITAKITA FS more than once. The sampling technique used in this study is simple random sampling. Data collection is done using a questionnaire distributed to 156 respondents. The results of the study show that service quality and price have a significant effect on customer satisfaction. The results of this study are used to improve service quality and prices of KITAKITA FS that have not met customer satisfaction.